Pengaruh Gaya Kepemimpinan, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Jajaran Polres Boyolali - Sakti, Febriyan Adi Garuda (2016)
This Research is to analyze how head of police Boyolali in leading all personnel, knowing influence of discipline work, and know environmental influence work to all the personnel to performance of the police personnel Boyolali. Variable of Research used in this research variable dependent (Y) in the form of performance of independent personnel variable and (X) in the form of leadership style (X1), discipline work (X2), and the environment work (X3). Population in this research entire personnel exist in police Boyolali. Where method of determination of sample use technique of random of random sampling or sampling modestly. So that from population as much 380 personnel obtained 100 personnel as sample. Data of this research use data of primary obtained direct the than 100 people of sample as responder. examination of Hypothesis in this research use technique test doubled linear regression, test t and test F constructively software SPSS 16. Where examination of hypothesis use level of signifikansi equal to 0,05. Pursuant to result of examination statistically can be seen clearly that by partial all free variable have an effect on to variable trussed. Influence given third the free variable have the character of positive meaning excelsior of leadership style, discipline work and the environment work hence result excelsior also performance of yielded personnel. The result as according to raised hypothesis. This matter shown with the result test doubled linear regression that is equation Y = 2,628 + 0,191 X1 + 0,299 X2 + 0,368 X3 e. Where matter [of] this means that if [there] no leadership style, discipline work, and the environment work, hence the performance [is] equal to 2,628.